MANAGEMENT OF STUDENTS’ LEARNING ACTIVITIES BY MEANS OF DISTANCE LEARNING: MOTIVATIONAL ASPECT - Kucheriavyi, Andrii; Buryi, Serhii; Atamanchuk, Yurii (Revista Inclusiones, 2020)
The article is devoted to solving the problem of discrepancy between the traditional practice of using distance courses in high school and the potential of their application to solve the managerial tasks of motivational content. The purpose of the study is to determine the requirements of the management representatives of training in high school for distance courses as a means of forming students’ motives for learning and opening opportunities for their realization, the achievement of which requires prior study of relevant theoretical materials and practical experience. These requirements are considered at four levels of government. The level of pedagogical management (of a teacher) meets the requirements regarding the formation of students’ motivation for different types of educational activities, mastering the training course in general, etc.